Perceptions of motivational interviewing: validation of the client evaluation of motivational interviewing scale with probation clients - Armstrong, Gaylene Styve (Criminal justice and behavior, 2016)
The practice of motivational interviewing (MI) has gained acceptance as an effective approach to support behavior change in various therapeutic contexts. In recent years, MI has been extended to clients within less traditional therapeutic settings including prisons and probation departments. Despite the known strengths of MI for positively affecting behavioral change in therapeutic contexts, the extent to which probation officers are able to effectively utilize MI remains unknown. The current study utilizes self-report responses from 485 probationers to assess the internal consistency and factor structure of the Client Evaluation of Motivational Interviewing (CEMI) as a tool for gathering feedback on MI fidelity in probation. Confirmatory factor analysis found two distinct MI factors to exist among this client base?technical and relational aspects of MI. Results suggest the CEMI is an effective tool to determine community corrections clients? self-perceptions of probation officer?s use of MI-consistent techniques.